RURAL-URBAN CLASSIFICATION AND MUNICIPALGOVERNANCE IN INDIA - Ram B. Bhagat (Singapore Journal of Tropical Geography, 26(1), 2005, 61-73, 2005)
Rural-urban classification constitutes an important framework for the collection and compilationof population data in many countries. While "urban" is often specifically defined, "rural" istreated simply as a residual category. The criteria defining urban also differ from country tocountry. This paper argues that these rural and urban statistical categories are also highly significantfor local governance, increasingly so in recent years given the emphasis on local governance andits restructuring. In India, constitutional amendments have given constitutional status to localbodies in the federal structure of the country. Local bodies are thus now expected to draw up theirown plans and initiate development works, which requires them to generate their own resourcesand lessen their dependence on central government funding. It is thus necessary to reorganiseurban space into viable spatial units in terms of their revenue base. While rural-urban classificationis the task of the Census of India, state governments are responsible for granting municipal statusto urban centres. This paper examines the criteria and limitations of the rural-urban classificationfollowed by the Census, its congruence with the dynamics of state-accorded municipal/non-municipal status and some implications for municipal governance in India.